Antimicrobial activity of macroalgae from Kwazulu-Natal, South Africa, and the isolation of a bioactive compound from Osmundaria serrata (Rhodophyta) - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (PhD (Botany))--University of Pretoria, 2006.